Other Country : Barry Lopez and the Community of Artists - Warren, James Perrin (Book collections on Project MUSE., 2015)
"A deep concern with landscape, animals, indigenous cultures, and essential moral values runs through Other Country as author James Perrin Warren reveals the dynamic relationship between Barry Lopez and the artistic community in their quest to lead cultural change"--Provided by publisher.